Efektifitas Corporate Governance ,Corporate Social Responsibility, dan Earning Management Terhadap Nilai Perusahaan (Perspektif Expectacy Theory dan Agency Theory) - Pancawati Hardiningsih; Rachmawati Meita Oktaviani (Conference In Business, Accounting, And Management (CBAM), 2012)
This research aimed to analyze the effect of Corporate Governance, Corporate Social Responsibility, and Earning Management to corporate value after the issuance of UU No. 40 in 2007 about Perseroan Terbatas regarding Limited Liability Company in manufacturing companies on the Stock Exchange with the perspective of Agency Theory and Expectancy Theory. The research proved that Corporate Governance has not effect on Corporate Value,while Corporate Social Responsibility affects Corporate Value,and Earning Management affect on Corporate Value. Corporate Governance proved not as moderating variable on Corporate Social Responsibility and Corporate Value. Corporate Governance proved to be a moderating variable on Earning Management and Corporate Value. This study supports the Agency Theory and Expectancy Theory, which describes how a company enhance Corporate Value. Keywords: Corporate Governance, Corporate Social Responsibility, Earning Management, Corporate Value